Faktor Pendidikan Anggota Koperasi dalam Meningkatkan Partisipasi Anggota Sebagai Pemilik Dan Pelanggan - Gunawan, Ujang (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2018)
The result of partial test and simultaneously are indicating that there was positive and significant effect of the learning material, method and media, trainers, against the members of participant on Koperasi Kojamas and learning material is determinant factor than others. In other word, the better learning material, more effective of the method and media which being used, the more competence skill which trainers has and participant in the class, more the highest of the participation members should be.